2022
DOI: 10.3389/fonc.2022.877147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Galanin Expression in Colorectal Cancer: An Immunohistochemical and Transcriptomic Study

Abstract: Colorectal cancer (CRC) represents around 10% of all cancers, with an increasing incidence in the younger age group. The gut is considered a unique organ with its distinctive neuronal supply. The neuropeptide, human galanin, is widely distributed in the colon and expressed in many cancers, including the CRC. The current study aimed to explore the role of galanin at different stages of CRC. Eighty-one CRC cases (TNM stages I – IV) were recruited, and formalin-fixed paraffin-embedded samples were analyzed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The data show that the expression of GAL is related to CRC aggressive behavior and it seems that CRC cells showing a high GAL expression are more malignant and are also involved in the recurrence of the tumor [ 180 ]. However, a recent study has shown that GAL downregulation is correlated with advanced CRC stages in northern African individuals and it is linked to autophagy, cell cycle and division, immune system response and the transcriptional regulation of TP53 [ 183 ]. Compared to epithelial cells of the large intestine, a stronger immunoreactivity for GAL 1 R/GAL 3 R was observed in CRC cells and it has been reported that the high expression of GAL 3 R in CRC tissue was associated with a better prognosis and longer survival of CRC patients; this means that GAL 3 R is a prognostic factor for these patients [ 184 ].…”
Section: The Galaninergic System and Cancermentioning
confidence: 99%
“…The data show that the expression of GAL is related to CRC aggressive behavior and it seems that CRC cells showing a high GAL expression are more malignant and are also involved in the recurrence of the tumor [ 180 ]. However, a recent study has shown that GAL downregulation is correlated with advanced CRC stages in northern African individuals and it is linked to autophagy, cell cycle and division, immune system response and the transcriptional regulation of TP53 [ 183 ]. Compared to epithelial cells of the large intestine, a stronger immunoreactivity for GAL 1 R/GAL 3 R was observed in CRC cells and it has been reported that the high expression of GAL 3 R in CRC tissue was associated with a better prognosis and longer survival of CRC patients; this means that GAL 3 R is a prognostic factor for these patients [ 184 ].…”
Section: The Galaninergic System and Cancermentioning
confidence: 99%
“…We found that differentially expressed mRNAs are involved in positive regulation of the cell proliferation process. Upregulated genes such as DHRS2, ID2 [ 32 ], CCNA1 [ 33 ], EGR2 [ 34 ], WNT4 [ 35 ], RIPK4 [ 36 ], PDK4 [ 37 ], IL-11 [ 38 ], and MAPK4 play a role in promoting the development of colon cancer and various malignancies [ 39 ]. IL-16 plays a role in promoting cellular inflammation [ 40 ]; BCl-6 plays a role in inhibiting apoptosis in colon cancer cells [ 41 ]; and NFKBIZ plays a role in promoting the expression of the IL-17 inflammatory signaling pathway [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of CCNB1 expression has also been reported to inactivate PI3K/AKT signaling and induce G2/M arrest ( Meng et al, 2023 ). Moreover, elevated CCNA1 and CCNA2 expression levels activates the PI3K/AKT pathway, promoting tumor growth and cell survival ( Talaat et al, 2022 ). MCM5 is a chromatin-binding protein that serves as a diagnostic marker for CRC, regulating tumor cell proliferation and cell cycle progression ( Dai et al, 2017 ; Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%